The Anti-Ottoman-German Alliance Propaganda in French Humor Magazines during the First World War - Çakı, Caner; Darı, Abdülhakim Bahadır (Fırat University, 2024)
During the First World War, harsh anti-alliance propaganda was made by publishing cartoons directly targeting Ottoman-German Alliance on covers of Le Cri de Paris and Le Rire, two important humor magazines of French humor. Considering that both magazines served as France's propaganda tools during this period, it can be said that magazines' anti-Ottoman-German Alliance cartoons were important in terms of reflecting France's view of the Ottoman-German Alliance. The study aimed to determine how French humor magazines presented both countries in their propaganda against the Ottoman-German Alliance in the First World War and what messages they gave against both countries. For this purpose, in the study, cartoons on the subject were examined using semiotic method in the light of Roman Jakobson's Communication Functions. In the study, it was found that Le Cri de Paris pointed out that Germany used Ottoman Empire in line with its interests and that Ottoman Empire wasn’t happy with alliance, while Le Rire pointed out that Ottoman Empire came under the direct control of Germany with the alliance and that alliance was to the detriment of Ottoman Empire. In this way, it was concluded in the study that both magazines mainly targeted Germany through anti-alliance propaganda.

Birinci Dünya Savaşı’nda Fransız mizahının iki önemli mizah dergisi Le Cri de Paris ve Le Rire’in kapaklarında doğrudan Osmanlı-Alman İttifakı’na yönelik karikatürler yayımlanarak ittifak karşıtı sert bir propaganda gerçekleştirilmiştir. Bu dönemde her iki derginin de Fransa’nın propaganda aracı olarak hizmet ettiği düşünüldüğünde dergilerin Osmanlı-Alman İttifakı karşıtı karikatürlerinin Fransa’nın Osmanlı-Alman İttifakı’na bakışını yansıtması bakımından önem taşıdığı söylenebilmektedir. Çalışmada Fransız mizah dergilerinin Birinci Dünya Savaşı’nda Osmanlı-Alman İttifakı karşıtı propagandasında her iki ülkeyi ne şekilde sunduğunun ve her iki ülkeye karşı hangi mesajlar verdiğinin tespit edilmesi amaçlanmıştır. Bu amaçla çalışmada konuya ilişkin karikatürler, Roman Jakobson’un İletişim İşlevleri ışığında göstergebilim yöntemi kullanılarak incelenmiştir. Çalışmada Le Cri de Paris’de Almanya’nın çıkarları doğrultusunda Osmanlı İmparatorluğu’nu kullandığına ve ittifaktan Osmanlı İmparatorluğu’nun memnun olmadığına, Le Rire’de ise Osmanlı İmparatorluğu’nun ittifakla birlikte doğrudan Almanya’nın güdümüne girdiğine ve ittifakın Osmanlı İmparatorluğu’nun zararına olduğuna yönelik mesajlar verildiği bulgularına ulaşılmıştır. Bu şekilde çalışmada her iki derginin de ittifak karşıtı propaganda üzerinden ağırlıklı olarak Almanya’yı hedef aldığı sonucuna ulaşılmıştır.
BİRİNCİ DÜNYA SAVAŞI’NDA FRANSIZ MİZAH DERGİLERİNDE OSMANLI-ALMAN İTTİFAKI KARŞITI PROPAGANDA
Keywords: Cultural Studies (Other); Kültürel çalışmalar (Diğer)